Madison Avenue and the color line : African Americans in the advertising industry - Chambers, Jason (EBL-Schweitzer, 2008)
"For much of the twentieth century, even as advertisers chased African American consumer dollars, the doors to most advertising agencies were firmly closed to African American professionals. Over time, black participation in the industry resulted from the combined efforts of black media, civil rights groups, black consumers, government organizations, and black advertising and marketing professionals working outside white agencies. Blacks positioned themselves for jobs within the advertising industry, especially as experts on the black consumer market, and then used their status to alter stereotypical perceptions of black consumers. By doing so, they became part of the broader effort to build an African American professional and entrepreneurial class and to challenge the negative portrayals of blacks in American culture." "Using an extensive review of advertising trade journals, government documents, and organizational papers, as well as personal interviews and the advertisements themselves, Jason Chambers weaves individual biographies together with broader events in U.S. history to tell how blacks struggled to bring equality to the advertising industry."--Jacket